Feeling Good by Doing Good: Employee CSR-Induced Attributions, Job Satisfaction, and the Role of Charismatic Leadership - Vlachos, Pavlos A.; Panagopoulos, Nikolaos G.; Rapp, Adam A. (2013)
Interest in corporate social responsibility (CSR) is gaining momentum in academic and managerial circles. However, prior work in the area has paid little attention to how CSR initiatives should be implemented inside the organization. Against this backdrop, this study examines the impact of CSR initiatives on an important stakeholder group—employees. We build and test a comprehensive multilevel framework that focuses on whether employees derive job satisfaction from CSR programs. The proposed model predicts that a manager’s charismatic leadership influences employees’ interpretations about the motives underlying their companies’ engagement in CSR initiatives (intrinsic and extrinsic CSR-induced attributions) which, in turn, influence employee job satisfaction. Hierarchical linear modeling of data from 47 organizational units comprising 438 employees from three world-leading manufacturing organizations shows that when employees think that their manager possesses charismatic leadership qualities, they tend to attribute the organization’s motives for engaging in CSR activities to intrinsic values, which, in turn, are positively associated with job satisfaction. Also, the extent to which managers are perceived as charismatic leaders relates positively to job satisfaction. Interestingly, CSR-induced extrinsic attributions are neither explained by charismatic leadership nor do they predict job satisfaction. Implications for both theory and practice are discussed.
Keywords: Employees; Attribution Theory; Motives; Corporate Social Responsibility; Charismatic Leadership